Effect of chemical and organic fertilization on soil carbon and nitrogen accumulation in a newly cultivated farmland - Rong YANG; Yong-zhong SU; Tao WANG; Qin YANG (Journal of Integrative Agriculture, 2016)
Increased food demand from the rapidly growing human population has caused intensive land transition from desert to farmland in arid regions of northwest China. In this developing ecosystem, the optimized fertilization strategies are becoming an urgent need for sustainable crop productivity, efficient resources use, together with the delivery of ecosystems services including soil carbon (C) and nitrogen (N) accumulation. Through a 7-year field experiment with 9 fertilization treatments in a newly cultivated farmland, we tested whether different fertilizations had significant influences on soil C and N accumulation in this developing ecosystem, and also investigated possible mechanisms for this influence. The results showed that applying organic manure in cultivated farmland significantly increased the soil C and N accumulation rates; this influence was greater when it was combined with chemical fertilizer, accumulating 2.01 t C and 0.11 t N ha–1 yr–1 in the most successful fertilization treatment. These high rates of C and N accumulation were found associated with increased input of C and N, although the relationship between the N accumulation rate and N input was not significant. The improved soil physical properties was observed under only organic manure and integrated fertilization treatments, and the significant relationship between soil C or N and soil physical properties were also found in this study. The results suggest that in newly cultivated farmland, long term organic manure and integrated fertilization can yield significant benefits for soil C and N accumulation, and deliver additional influence on physical properties.